Answer:
(x - 3)(5x - 3)
Explanation:
Assuming you require the expression to be factorised.
Given
5x² - 18x + 9
Consider the factors of the product of the coefficient of the x² term and the constant term which sum to give the coefficient of the x- term.
product = 5 × 9 = 45 and sum = - 18
The factors are - 15 and - 3
Use these factors to split the x- term
5x² - 15x - 3x + 9 ( factor the first/second and third/fourth terms )
= 5x(x - 3) - 3(x - 3) ← factor out (x - 3) from each term
= (x - 3)(5x - 3) ← in factored form